Distance learning as a strategic channel for the development of tutoring services - Grigorievna, Bondarenko Tatiana; Alekseevna, Prodanova Natalia; Sotnikova, Lyudmila Viktorovna (Linguistics and Culture Review, 2021)
This article is devoted to the development of distance learning, namely, the possibilities for the development of additional education, corporate training and tutoring business. The events of March-May 2020 gave impetus to the development of distance education, schools and universities were transferred to online learning. The authors emphasize that, despite the ideal external conditions for the development of distance education, the success of this business also depends on the typology and specialization of distance education. The authors present the features of the development of distance education by country. To understand the possibility and readiness of the development of online education in the Russian Federation, the authors carried out a SWOT analysis and a PEST analysis according to the content of the passport of the National Project "Education".